Accumulation of beryllium and its effects on hydrogen retention in tungsten divertor. (3rd August 2018) - He, Zhihai; He, H.Y.; Chen, J.L.; Ding, R.; Pan, B.C.
Abstract: Tungsten (W) and beryllium (Be), as superiorly structural materials, may mutually permeate into each other when used as the plasma-facing materials in a fusion reactor, and interact with hydrogen (H) which commonly exists in the fusion environment. By performing first-principles calculations, we investigate the interactions among W, Be and H in W materials. We find that multiple (up to 10) Be atoms can dissolve in W monovacancy to form n Be- V W complexes, and these complexes can decrease the formation energy of a vacancy nearby, which in turn promotes the growth of n Be- V W complexes. The presence of the n Be- V W complexes reduces the retention of H in vacancy. However, we also find that a small amount of Be dissolved in the small-angle tilt grain boundary (GB) has no obvious influence on H retention, while a large amount of Be will promote the growth of cavities in the GB regions. In addition, the adsorbed Be atoms on W (0 0 1) surface are energetically favorable to aggregate together and form a monolayer structure. The presence of Be atomic layer can weaken the adsorption of H on W surface. This work provides a fundamental insight for understanding the accumulation of Be in W, as well as its effects on H retention. This work did not deal with the case relevant to the Be–W alloying phase, which requires further study.